Association of Chronic Pain and Community Integration of Returning Veterans With and Without Traumatic Brain Injury. Issue 1 (January 2016) - Wu, Emily; Graham, David P.
Abstract : Objective: To evaluate the association between community integration and pain in veterans with and without mild blast-related traumatic brain injury (TBI). Design and Participants: A cross-sectional study of 198 Operation Enduring Freedom/Operation Iraqi Freedom veterans, 135 with mild TBI and 63 without TBI exposure. Main Measures: Community Integration Questionnaire (CIQ), Community Reintegration of Injured Service Members Instrument, Brief Pain Inventory. Results: Pain interference was significantly associated with CIQ social integration ( P = .037), and pain severity was significantly associated with CIQ home integration ( P = .038) and CIQ social integration ( P = .044). Pain interference and pain severity had a significant interaction as related to the CIQ total score ( P = .046), CIQ job score ( P = .034), and CIQ productivity score ( P = .034). Pain interference ( P = .042) and pain severity ( P = .015) were associated with community participation, but not perceived limitations ( P > .05) or satisfaction ( P > .05) as measures by the Community Reintegration of Injured Service Members Instrument. There was a significant interaction between TBI status and pain severity ( P = .021) with community participation. Conclusions: Chronic pain has a negative association with the community integration of returning veterans. Although TBI status was associated with overall community integration ratings, depression had a stronger association with impairments. These findings suggest, above and beyond the treatment of depression, the importance of effectively managing TBI-related pain to foster improved social functioning and to promote the psychological and social well-being of returning veterans.